Integrated Metabolome and Transcriptome Analysis Uncovers the Role of Anthocyanin Metabolism in Michelia maudiae - Xiaoan Lang; Na Li; Lingfei Li; Shouzhou Zhang (International Journal of Genomics)
Michelia maudiae Dunn is one of the important ornamental plants in the Magnoliaceae family, and the color of its flowers usually appears naturally pure white. The discovery of a rubellis flower named M. maudiae Dunn var. rubicunda provides an opportunity to reveal the metabolism of the flavonoids and anthocyanins of this “early angiosperm” plant. Combined metabolome and transcriptome analyses were applied using white and rubellis mutant tepals. Seven stages have been divided for flower development, and forty-eight differentially altered metabolites were identified between white and rubellis tepals at a later stage. The major anthocyanins including peonidin O-hexoside, cyanidin O-syringic acid, cyanidin 3,5-O-diglucoside, cyanidin 3-O-glucoside, and pelargonidin 3-O-glucoside were upregulated over 157-fold in the mutant. Conversely, the highly significant accumulation of the colorless procyanidin or the slightly yellow epicatechin and catechin was found in white flowers. Putative homologues of color-related genes involved in the phenylpropanoid and flavonoid biosynthesis pathway were identified in the transcriptome. The increasing expression of dihydroflavonol 4-reductase (DFR) might play an important role in the occurrence of rubellis pigments, while the overexpression of anthocyanidin reductase (ANR) in white flowers may promote the biosynthesis of proanthocyanidins. Additionally, several coloration-related repressor R2R3-MYB transcription factors showed different expression levels in the tepals of the rubellis mutant. This study provides a comprehensive analysis relating color compounds to gene expression profiles of the Magnoliids plant M. maudiae. The newly generated information will provide a profound effect on horticultural applications of Magnoliaceae.